A Four Sector Econometric Model of the Canadian Economy - Hiroki Tsurumi (Queen's University, Department of Economics, 1969)
Earlier the author, together with his collegue, developed a growth model of the Canadian economy (9) which concentrated on the Gross Domestic Product (GDP) side, and from this earlier experience it was found desirable to incorporate not only the GDP side but also the gross national expenditure (GNE) and gross national product (GNP) sides. The present paper has evolved out of these considerations as well as it revises some of the behavioral equations of the earlier model.
Keywords: 330